2017
DOI: 10.1111/jgh.13852
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin has minor effects on bacterial composition, inflammation, and bacterial translocation in cirrhosis: A randomized trial

Abstract: Four weeks of treatment with rifaximin had no impact on the inflammatory state and only minor effects on BT and intestinal bacterial composition in stable, decompensated cirrhosis (NCT01769040).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 50 publications
5
60
0
1
Order By: Relevance
“…However, the use of these medications is so widely implemented in patients with cirrhosis that it would be extremely difficult to find patients with advanced cirrhosis without any of these confounders, and such patients would be an anomaly not reflecting the reality of patients with decompensated cirrhosis in terms of microbiota composition. Furthermore, recent studies suggest that several of these treatments do not have the anticipated major impact on microbiota composition, suggesting that the abnormalities in the cirrhosis microbiota are more related to the disease itself than to the medications received by these patients. Indeed, in our present study the severity of disease was more informative than treatment with antibiotics, lactulose or PPIs in explaining the variation in composition of the samples, or the changes in SCFAs production, but our small sample size does not allow us to answer this question.…”
Section: Discussionsupporting
confidence: 90%
“…However, the use of these medications is so widely implemented in patients with cirrhosis that it would be extremely difficult to find patients with advanced cirrhosis without any of these confounders, and such patients would be an anomaly not reflecting the reality of patients with decompensated cirrhosis in terms of microbiota composition. Furthermore, recent studies suggest that several of these treatments do not have the anticipated major impact on microbiota composition, suggesting that the abnormalities in the cirrhosis microbiota are more related to the disease itself than to the medications received by these patients. Indeed, in our present study the severity of disease was more informative than treatment with antibiotics, lactulose or PPIs in explaining the variation in composition of the samples, or the changes in SCFAs production, but our small sample size does not allow us to answer this question.…”
Section: Discussionsupporting
confidence: 90%
“…However, the findings remain unconvincing to date. In some studies, rifaximin showed a major preventive effect [62,63], while in others, this effect could not be determined or was only minor [64,65]. Thus, while there is some evidence that some patients might benefit from rifaximin, a better selection and stratification of patients is required in the clinical setting.…”
Section: Poorly Absorbable Antibiotics As Gut-liver Axis Interventionmentioning
confidence: 99%
“…Of note, a doubleblinded randomized control trial with 54 patients could not confirm these beneficial effects [29••]. Furthermore, Rifaximin seems to have only minor effects on bacterial composition, inflammation, and bacterial translocation [30]. Nevertheless, a combination of Rifaximin and Propanolol seem to be promising, probably due to additive effects of Rifaximin compared with NSBB monotherapy with decreased incidence of side effects due to lower NSBB dose than used normally as shown by an open-label randomized (2:1) trial in 73 patients [31].…”
Section: Current Concepts In the Clinicsmentioning
confidence: 99%